Analysis of Student Satisfaction with Learning Process Facilities and Services - Achmad Tarmizi; Dwi Aprillita (Sean Institute, 2024)
This research analyzes student satisfaction with facilities and services in the learning process, using surveys and interviews with students at Dian Nusantara University, Jakarta. Samples are selected randomly. The research instrument is a questionnaire and interview guide designed to measure critical aspects of student satisfaction, including physical facilities, learning technology, lecturer support, and administrative processes. The results of data analysis using descriptive statistical methods and factor analysis highlight students' perceptions of the advantages and disadvantages of the University education system. Recommendations include concrete steps to improve the quality of learning process facilities and services, hoping to impact the experience positively. I hope this research can positively contribute to improving the quality of education at Dian Nusantara University